EFFECTS OF A SHORT TERM PLYOMETRIC TRAINING PROGRAM OF AGILITY IN YOUNG BASKETBALL PLAYERS - Baljinder Singh Bal (Brazilian Journal of Biomotricity, 2011)
The aim of the study is to assess the effects of a short term plyometric training program of agility in young basketball players. A group of Thirty (N=30) male basketball players aged 18 - 24 years, who participated in intercollege basketball competitions organized by the Department of Sports, Guru Nanak Dev University, volunteered to participate in this study. Their mean height, weight, and age were 1.87±0.06m, 75.5± 5.2kg, 22.5± 0.4 years. All subjects, after having been informed about the objective and protocol of the study, gave their written consents and the study was approved by the local Committee of Ethics. The subjects were randomly assigned into two groups: experimental (E; n = 15) and control (C; n = 15). Group E was subjected to a 6- week training, 25 min a day. Student's t-test for independent data was used to assess the between-group differences and for dependent data to assess the Post-Pre differences. Level of p¿0.05 was considered significant. The results from our study are very encouraging and demonstrate the benefits of short term plyometric training program of agility in young basketball players. It is concluded that the use of plyometrics training program not only to break the monotony of training, but they can also improve the strength of basketball players.